Frequency of multisite non-hand joint involvement in patients with thumb-base osteoarthritis, and associations with functional and patient-reported outcomes - Anthony V. Perruccio; Elizabeth M. Badley; Daniel Antflek; J Denise Power; Heather Baltzer (Osteoarthritis and Cartilage Open, 2023)
Purpose: In OA studies, the focus often is on an index-joint; other affected joint sites are often overlooked. In this thumb-base OA study, we documented the frequency of symptomatic non-hand joint sites and investigated whether their count was associated with thumb-specific functional and patient-reported outcome measures. Design: Patients seeking care for thumb-base OA (conservative or surgical) were included. A patient-completed questionnaire captured sociodemographic and health characteristics, symptomatic hand and non-hand joint sites, and outcome measures (thumb-base pain intensity, symptoms and disability (TASD) and upper-extremity disability/symptoms (quickDASH)). Grip and pinch strength were measured. Linear regressions examined the association between each outcome and symptomatic joint site count, adjusted for several covariates. Results: The mean age of the 145 patients was 62 years, 72% were female. Mean symptomatic non-hand joint site count was 3.6. Ten percent reported only their hands as symptomatic; 30% reported 2–3 other symptomatic sites, and 49% reported 4+. From cross-sectional multivariable analyses, a higher symptomatic non-hand joint site count was associated with worse scores for all patient-reported outcomes and grip strength. Every unit increase in joint site count (49% had a 4+ count) was associated with a 2.1–3.3 unit increase (worse) in patient-reported outcome scores (all p ​< ​0.02). Conclusions: In this sample, nearly 80% of patients had 2+ symptomatic non-hand joint sites. These symptoms were associated with worse thumb- and hand-specific outcomes, suggesting a need for awareness of whole body OA burden, with implications for outcome score interpretations, study designs, and provision of care in thumb-base OA.